2017
DOI: 10.1002/ca.22889
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of medical students in Europe toward the clinical importance of histology

Abstract: Many studies have been undertaken to assess the attitudes of medical students to the clinical importance of gross anatomy. However, much less is known about their attitudes toward the clinical importance of histology. Using Thurstone and Chave methods to assess attitudes, over 2,000 early stage medical students across Europe provided responses to a survey that tested the hypothesis that the students have a high regard for histology's clinical relevance. Regardless of the university and country surveyed, and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Moreover, integration of histology into clinical context was tested and it proved to be successful (Singh, 2011;Shaw & Friedman, 2012;Malau-Aduli et al, 2013). However, more effort is needed to change students' attitudes toward the clinical importance of histology (Moxham et al, 2017). From pathology point of view, many integrated curricula have been tested and used in an attempt to reach maximal students' retention of the pathology knowledge they need in their clinical practice (Haspel et al, 2012;Malau-Aduli et al;Atukorala & Atapattu, 2015;Lisk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, integration of histology into clinical context was tested and it proved to be successful (Singh, 2011;Shaw & Friedman, 2012;Malau-Aduli et al, 2013). However, more effort is needed to change students' attitudes toward the clinical importance of histology (Moxham et al, 2017). From pathology point of view, many integrated curricula have been tested and used in an attempt to reach maximal students' retention of the pathology knowledge they need in their clinical practice (Haspel et al, 2012;Malau-Aduli et al;Atukorala & Atapattu, 2015;Lisk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The motivation of Dentistry students. Dentistry students find it less important to study histology compared to anatomy, though more necessary than embryology, as confirmed by other authors [11]. Although, histology plays a significant role in dentistry education from the point of view of assessing both normal structure and pathological changes Skills building session for dentistry students.…”
mentioning
confidence: 70%
“…Though dissection remains a mainstay in the process of anatomy teaching, several institutions have advocated its removal from modern teaching medical and allied health curricula for the following reasons: reduced allocated time for dissection, limited availability of resources, lack of possible donors, unpleasant smell of cadavers and shift towards the use of modern technologies in teaching [9,[15][16][17][18][19]. This led to a debate among anatomists regarding the optimal method for delivering anatomy to medical students and their desired degree of anatomical competence.…”
Section: Discussionmentioning
confidence: 99%